Transformation is back! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
World development report 2003: Sustainable development in a dynamic world: Transforming institutions, growth, and quality of life Published by Oxford University Press & World Bank, 2002. 272 pp. ISBN 0 8213 5150 8 US$ 26 Euro 24.10